Advanced decision support system for postoperative care unit using artificial neural networks - Subramanian, K. (Institute of Advanced Scientific Research, Inc., 2019)
Information technologies have become a vital element of everyday humanâs life. It makes them easy to handle the decision making problems with a healthcare environment. Currently, the utilization of artificial neural networks ofthe medical domain is high in demand. This paper addresses the issue of delay in postoperative care decision making process of the hospital due to inadequate approaches. It discusses and proposes an intelligent approach using artificial neural network technology for postoperative care decision making from the clinical database. Feed the clinical and surgery data into the neural network to get train and predict the appropriate decisions from three different options which are (a) the patient may go home, (b) the patient go the general ward and (c) the patient needs to be transferred to the intensive care unit. Besides, developed the prototype system to test and validate the proposed decision making support system with 200 medical data. The accuracy of the result obtained very high which is 96.15 percentages. This approach will assist physicians, nurse and healthcare providers to take appropriate postoperative care decision for saving patientâs life. Â© 2019, Institute of Advanced Scientific Research, Inc.. All rights reserved.